2019
DOI: 10.1101/863357
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Late life metformin treatment limits cell survival and shortens lifespan by triggering an aging-associated failure of energy metabolism

Abstract: 18The diabetes drug metformin is to be clinically tested in aged humans to achieve health 19 span extension, but little is known about responses of old non-diabetic individuals to this 20 drug. By in vitro and in vivo tests we found that metformin shortens life span and limits 21 cell survival when provided in late life, contrary to its positive early life effects. 22 Mechanistically, metformin exacerbates aging-associated mitochondrial dysfunction 23 towards respiratory failure, aggravated by the inability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
3
0
1
Order By: Relevance
“…It was already shown that the time when treatment administration starts can have a major impact on the effect of a compound. The prominent health-and lifespan-prolonging abilities of metformin, for instance, were recently verified in C. elegans when starting the treatment at the 1st day of adulthood, but resulted in opposite effects when starting at the 10th day of adulthood (Espada et al 2019). Interestingly, lifelong treatment with metformin slightly increased mean lifespan of female mice, but surprisingly decreased lifespan in male mice (Anisimov et al 2010;Blagosklonny 2010).…”
Section: Age At Compound Exposure and Phenotypic Measurements Mattersmentioning
confidence: 90%
“…It was already shown that the time when treatment administration starts can have a major impact on the effect of a compound. The prominent health-and lifespan-prolonging abilities of metformin, for instance, were recently verified in C. elegans when starting the treatment at the 1st day of adulthood, but resulted in opposite effects when starting at the 10th day of adulthood (Espada et al 2019). Interestingly, lifelong treatment with metformin slightly increased mean lifespan of female mice, but surprisingly decreased lifespan in male mice (Anisimov et al 2010;Blagosklonny 2010).…”
Section: Age At Compound Exposure and Phenotypic Measurements Mattersmentioning
confidence: 90%
“…Given that hormetic effects have been attributed to an overcompensation of homeostasis-regulating mechanisms and may thus rely on the capacity to maintain homeostasis [ 32 ], the absence of effects on maximum lifespan in some studies may indicate that very old individuals are unable to maintain homeostasis in response to biological stress, possibly due to a loss of resilience. Consistent with this possibility, feeding C. elegans with metformin late in life produces toxic effects and reduces lifespan by exacerbating age-related mitochondrial dysfunction [ 33 ], unlike the lifespan-enhancing effects of metformin seen in younger worms. Similarly, the lifespan-extension effects of EGCG decline with age [ 27 ].…”
Section: Lifespan Extension Occurs Via Hormesismentioning
confidence: 99%
“…In a recent study, metformin was administered starting at different time points during the worm's lifespan. At Days 1 and 4 of adulthood, metformin, at all tested concentrations, extended the lifespan of the worm while at Day 10 it reduced lifespan at all tested concentrations [202]. At Day 8, the effect on lifespan was dose dependent.…”
Section: Age Of First Drug Exposurementioning
confidence: 87%